외식업체 비정규직원의 직무특성, 임파워먼트, 조직몰입과 조직시민행동간의 구조적 관계 - 김찬중(Chan-Jung Kim); 김용순(Yong-Soon Kim) (한국콘텐츠학회 논문지, 7(11), 2007)
The purpose of this study is completed on the concept of Job Characteristics, Empowerment, Organizational Commitment and Organizational Citizenship Behavior through approaching empirically to the present state by searching various mutual relations with Job Characteristics, Empowerment, Organizational Commitment and Organizational Citizenship Behavior. For the study, research data was collected from 20 food-service outlets in Seoul, each variable is measured by Likert's 7-point scale. The results were as follows; First, job characteristics has a positive influence on empowerment, organizational commitment. Second, empowerment haven't significant effect on organizational commitment. Third, empowerment has a positive influence on organizational citizenship behavior. Fourth, the subject of this study was limited to Seoul. For this reason, it is difficult to generalize the results of this study to the overall food -service contingent workers. 본 연구는 비정규직법의 차별시정 조항으로 인하여 비정규직원의 대량해고와 외주화의 사태가 예상됨에 따라 외식업체에 종사하는 비정규직원의 직무특성에 대한 지각, 임파워먼트, 조직몰입, 조직시민행동 간의 관계에 대한 보다 폭넓은 이해로 인적자원 관리적 측면에서 시사점을 도출해 보고자 실증분석을 실시하였다. 본 연구의 조사대상은 외식업체에 근무하고 있는 비정규직원으로 선정하였고, 그 중 서울지역에서 영업활동 중인 패밀리 레스토랑의 비정규직원을 표본으로 한정하여 조사하였다. 연구결과를 하면 다음과 같다. 첫째, 과업중요성과 기능다양성을 높게 지각할수록 임파워먼트와 조직몰입이 높아지는 것으로 나타나 가설이 지지되었다. 둘째, 임파워먼트와 조직몰입간의 관계는 유의미하지 않는 것으로 나타났다. 셋째, 임파워먼트는 조직시민행동에 정의 영향을 미치는 것으로 나타났다. 마지막으로 연구의 시사점과 한계 및 향후연구의 방향을 제시하였다.